Multiple intelligences in Japanese language learning. - Suan, Wei Hui; Sulaiman, Tajularipin (Common Ground Publishing, 2009)
The awareness of the multiple intelligences and the appreciation towards the specific intelligences optimizes motivation, and accelerates the learning process. Gardner (1999) claims that all individuals possess eight types of multiple intelligences, which are verbal-linguistic, logical-mathematical, music, visual-spatial, kinaesthetic, interpersonal, intrapersonal, and naturalistic intelligence. Understanding of these profiles may lead one to a better understanding of self and how individual learn. This study adopts a descriptive approach, using questionnaires as the means to collect data. The objectives of this paper are firstly to examine the learners' profile of multiple intelligences, determines the correlation among intelligences, and then to suggest the learning activities based on the multiple intelligences. As a result of this study, it was found that there were positive correlations among the variables, thereby suggesting alternative routes to effective Japanese language learning via more than two kinds of learning strategies.